Preparation And Characterization Of Monodimensional Oxide Ion Conductors In Bi2o3moo3 System - Lim, Chia Meng (2007)
A new family of mono-dimensional oxide ion conductors with a formula xBi2O3: MoO3 has been prepared by three different methods: solid state, mechanochemical and n-butylamine method. X-ray powder diffraction (XRPD) analysis showed that materials with compositions BixMo10Oδ (25.5 ≤ x ≤ 27.5) prepared by solid state method formed high-temperature (HT) phase after heating at 800oC for 48 hours. With mechanochemical and n-butylamine methods, the lower limit of solid solution was x = 25. In the mechanochemical method, HT-Bi26Mo10O69 was obtained after milling at 1400 rpm for 1 hour, followed by heating at 800oC for only 1 hour or 750oC for 24 hours. With n-butylamine method, the reaction product had to be heated at 800oC for 48 hours to yield a phase pure HT-Bi26Mo10O69. All the peaks in the XRPD patterns of HT-phase materials can be fully indexed in a monoclinic symmetry with space group P2/c. Materials of compositions 27 ≤ x ≤ 31 appears to form a low-temperature (LT) phase after being heated at 650oC for 48 hours. For LTphase materials, the XRPD patterns were fully indexed in a monoclinic symmetry with space group P21/a.Electrical properties of phase pure materials were determined using impedance spectroscopy. From the results, HT-Bi26Mo10O69 prepared by mechanochemical and n-butylamine methods exhibited higher conductivity values compared to that prepared via solid-state method in the temperature range of 200-300oC. HTBi27Mo10O70.5 prepared by solid state method exhibited highest conductivity among the HT-phase solid solutions. There was, however, no difference in conductivity for HT-Bi27Mo10O70.5 prepared by the three different methods. The high-temperature polymorph of Bi27Mo10O70.5 exhibited higher conductivity than the low-temperature polymorph. Doping was carried out on the Mo site of HT-Bi27Mo10O70.5 with selected dopants, i.e. Al, Cr, Ge, Si, Sn, Zr, As, Nb, Sb and W. All dopants could be introduced into Bi27Mo10O70.5 with rather limited solid solutions. Bi27Mo9.5Zr0.5O70 gave a conductivity value one order higher than the parent material Bi27Mo10O70.5. No significant difference in conductivity was observed for other doped materials compared to the parent material Bi27Mo10O70.5. The stoichiometric composition of phase pure materials was confirmed by inductively coupled plasma-optical emission spectrometry (ICP-OES). The phase transition of triclinic-monoclinic for HT-BixMO10Oδ (25.5 ≤ x ≤ 27) was observed in differential thermal analysis (DTA) and differential scanning calorimetry (DSC). No thermal event was observed for doped materials, except Bi27Mo9.8W0.2O70.5. No weight loss of phase pure materials was observed in the thermogravimetric analysis (TGA).Scanning electron microscopy (SEM) experiments showed that the grain size of single phase materials was in the range of 10 – 20 μm, with low porosity. The straight-line plots of density versus x in BixMo10Oδ solid solutions indicated that Vegard‟s law was obeyed. Absorptions in the far IR region (400 – 1000 cm-1) due to the vibration of Mo-O bond were observed in Fourier-transform infrared (FT-IR) spectroscopy.